105k views
4 votes
Which expression is equivalent to (g*h)(5)?

Which expression is equivalent to (g*h)(5)?-example-1
User Matskn
by
5.8k points

2 Answers

4 votes

For this case, we must perform a composition of functions.

Let two functions, f(x) and g(x). To find
(f_ {0} g) we calculate
f (g (x), that is, replace g (x) in f (x).

So, if we have:


h (x) = x-7\\g (x) = x ^ 2

And we want to find
(g_ {0} h) (x). We make:


g (h (x)) = (x-7) ^ 2

if we want the composite function evaluated at 5, we substitute
x = 5


g (h (5)) = (5-7) ^ 2

Answer:


g (h (5)) = (5-7) ^ 2

Option A

User Hyder
by
5.0k points
2 votes

Answer:(5-7)²


Step-by-step explanation: as h(x)=x-7 and g(x)=x²

so, goh(x)=g(h(x))

=g(x-7)

=(x-7)²

hence, goh(5)=(5-7)²


User Bkqc
by
5.2k points